Potato Cultivation Under Zero Tillage and Straw Mulching: Option for Land and Cropping System Intensification for Indian Sundarbans - Dey, Saikat; Sarkar, Sukamal; Dhar, Anannya; Brahmachari, Koushik; Ghosh, Argha; Goswami, Rupak; Mainuddin, Mohammed (Land (Basel), 2025)
Agriculture in the Indian Sundarbans deltaic region primarily depends on a rice-based monocropping system during the rainy season, with the subsequent season often remaining fallow. To mitigate this issue, a series of experiments using zero tillage and straw mulching (ZTSM) potato cultivation were conducted over eight consecutive years (2017–2024) across various islands in the Sundarbans Delta, West Bengal, aimed to intensify the cropping system and ensure the betterment of the land use pattern using climate-smart agricultural practices. In the initial two years, the experiments concentrated on assessing different potato cultivars and nutrient dosages under zero tillage and paddy straw mulching conditions. During the subsequent years, the focus shifted to field demonstrations under diverse climatic conditions. The research included the application of different macronutrients and growth regulators, in combination with different depths of straw mulching. In the final years of the study, the intervention was dedicated solely to the horizontal expansion of cultivated land. These initiatives aimed to enhance agricultural productivity and sustainable land use in the polders, promoting climate-resilient farming practices. From the sets of experiments, we standardized the sustainable nutrient management strategies and selection of appropriate potato cultivars vis-à-vis depth of straw mulching and, finally, the overall best agronomic practices for the region. The adoption of the ZTSM potato cultivation system demonstrated considerable success, as evidenced by the remarkable increase in the number of farmers employing this sustainable agricultural practice. The number of farmers practicing zero tillage potato cultivation surged from 23 in the initial year to over 1100, covering an area of more than 15 ha, highlighting the effectiveness of the technology. The analysis of the estimated adoption also showed that more than 90% adoption is likely to be achieved within a decade. This potential expansion underscores the benefits of the ZTSM potato cultivation system in improving soil health, conserving water, and reducing labour and costs. As more farmers recognize the advantages of zero tillage potato mulching, this approach is poised to play a pivotal role in sustainable agriculture, enhancing productivity while promoting environmental stewardship.